Genital warts incidence and healthcare resource utilisation in Australia. Issue 3 (3rd December 2009) - Pirotta, Marie; Stein, Alicia N; Conway, E Lynne; Harrison, Christopher; Britt, Helena; Garland, Suzanne
Abstract : Objectives: To estimate for the first time the incidence and healthcare resource utilisation associated with genital warts (GW) in Australia prior to the human papillomavirus vaccination programme. Method: The authors analysed data from the nationally representative Bettering the Evaluation of Care and Health general practice cross-sectional programme and from the National Hospital Morbidity Database to estimate age-related incidence and community (non-hospital) and hospital-related costs (in 2009 Australian dollars) associated with medical treatment of GW. Results: The authors estimated an annual incidence of 2.19 cases of GW per 1000 Australians (95% CI 1.88 to 2.49), with peak incidence in women aged 20–24 years at 8.61 cases per 1000 and in men aged 25–29 years at 7.40 cases per 1000. The estimated number of consultations per GW case was 2.9 (95% CI 2.5 to 3.3) for women and 2.8 (95% CI 2.3 to 3.2) for men. Ablative treatments in general practice were more common in men (60% of consultations) than in women (37% of consultations). In contrast, more women (16% vs 8%) were referred to specialists, and 75% of ablative procedures requiring hospitalisation were performed in women. The annual cost of management of GW is over A$14 million, with an estimated cost per treated case of A$251 for men and A$386 for women. Conclusions: GW impose a large health and cost burden on Australians. The national immunisation programme with the quadrivalent human papillomavirus vaccine has the potential to greatly reduce this burden, and future research measuring its impact is keenly anticipated.